Evaluation of biorational insecticides against capsule borers, Helicoverpa armigera and Heliothis peltigera (Lepidoptera: Noctuidae) on safflower: EVALUATION OF BIORATIONAL INSECTICIDES AGAINST CAPSULE BORERS ON SAFFLOWER - ASLAM,; M SHANKARA MURTHY,; A PRABHURAJ,; N M SUNILKUMAR,; SHIVALEELA,; B KISAN,; P MAHESWARA REDDY, (Journal of Oilseeds Research, 2022)
Safflower capsule borers, Helicoverpa armigera (Hübner) and Heliothis peltigera (Denis and Schiffmüller) (Lepidoptera: Noctuidae) were considered as economically important pests of safflower. The present study was undertaken to evaluate the biorational insecticides (chlorantraniliprole 18.5 SC @ 0.15 ml/l, Beauveria bassiana @ 4.0 g/l, Metarhizium rileyi @ 4.0 g/l, commercial B.t. (Dipel) @ 2.0 ml/l, commercial neem product 1500 ppm @ 2.0 ml/l and indoxacarb 15 EC @ 0.3 ml/l) against these pests on safflower during rabi 2020-21 at Krishi Vigyan Kendra, Bidar, Karnataka, India. The results indicated that all the treatments were superior over untreated check in reducing the capsule borers population. Among the tested products, chlorantraniliprole was found to be effective in suppression ofthe capsule borers, recorded lower population (0.11 larvae per plant) with higher yield (10.47 q/ha) and benefit cost ratio (1.96), followed by indoxacarb and commercial B.t. product, recorded 0.20 and 0.23 larvae/plant, 9.44 q/ha and 8.75 q/ha and benefit cost ratio of 1.82 and 1.63, respectively.